EMISI CO2 PADA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq) YANG DITUMPANGSARIKAN DENGAN TANAMAN PANGAN FASE BERBEDA DI TANAH MINERAL - Muhammad Misbahuddin; Ervina Aryanti; Endah Purnamasari; Indah Permanasari; Mokhamad Irfan; Ahmad Taufiq Arminudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Land changes become oil palm plantations accused of contributing greenhouse gas emissions (GHG) included in the mineral soil, therefore it is very important to gather information in mineral soil CO2 emissions to support mitigation and adaption to climate change. This purpose of this research determine the CO2 emissions in the oil palm plantations planted crops in the vegetative stage and generative phase, as well as to determine the ratio of CO2 emissions in the oil palm plantations planted crops in the vegetative stage and generative phase. This research was conducted in November 2015 to February 2016 in Subdistrict of Tambang, District of Kampar, Province Riau. The method used in this research was Random Block Design with four treatments and replications. The treatments were oil palm-bera, oil palm-corn, oil palm-soy bean, oil palm-intercropping corn soy bean. The research showed that CO2 emissions in the oil palm plantation intercropped with crops (corn and soybeans) in the vegetative phase showed no significantly different. Comparison large of CO2 emissions indicated oil palm-corn vegetative phase.